Spatial Multicriteria Evaluation for Mapping the Risk of Occurrence of Peste des Petits Ruminants in Eastern Africa and the Union of the Comoros - Ruget, Anne-Sophie; Tran, Annelise; Waret-Szkuta, Agnès; Moutroifi, Youssouf Ousseni; Charafouddine, Onzade; Cardinale, Eric; Cêtre-Sossah, Catherine; Chevalier, Véronique (Frontiers in Veterinary Science, 2019)
Peste des Petits Ruminants (PPR) is widely circulating in Africa and Asia. The disease is a huge burden for the economy and development of the affected countries. In eastern Africa, the disease is considered endemic. Because of the geographic proximity and existing trade between eastern African countries and the Comoros archipelago, this latter is at risk of introduction and spread, and the first PPR outbreaks occurred in the Union of the Comoros in 2012. The objective of this study was to map the areas suitable for PPR occurrence and spread in the Union of the Comoros and four eastern African countries, namely Ethiopia, Uganda, Kenya and Tanzania. A Geographic Information System (GIS)-based Multicriteria Evaluation (MCE) was developed. Risk factors for PPR occurrence and spread, and their relative importance, were identified using literature review and expert-based knowledge. Corresponding geographic data were collected, standardized and combined based on a weighted linear combination to obtain PPR suitability maps. The accuracy of the maps was assessed using outbreaks data from EMPRES database and a ROC curve analysis. Our model showed an excellent ability to distinguish between absence and presence of outbreaks in eastern Africa (AUC = 0.907; 95% CI [0.820-0.994]), and a very good performance in the Union of the Comoros (AUC = 0.889, 95% CI: [0.694-1]). These results highlight the efficiency of the GIS-MCE method, which can be applied at different geographic scales: continental, national and local. The resulting maps provide decision support tools for implementation of disease surveillance and control measures, thus contributing to the PPR eradication goal of OIE and FAO by 2030.